Evaluation of the risk of infection by COVID-19 in the Department of Valle del Cauca using a Technology of the information and communication tool - Valencia Cardona, Andres Felipe; Quintero, Carlos Alfredo Vargas; Triana, Lina; Jimenez, Juan Carlos; Jimenez, Antonio; Etayo, Julian; Ocampo, Carlos Hernan (Interdisciplinary Journal of Epidemiology and Public Health, 2023)
Introducción: The use of technology in the health area is applied through telemedicine and the use of applications for many activities. In our case in risk detection and patient prioritization to COVID-19. Objective: Document the experience in the mobile application use "VALLE CORONA" to COVID-19 and risk stratification. Methods: It is an operational and observational research. A mobile application was designed with 14 questions that were established according to the evidence and recommendations of experts and international institutions and the Colombian National Institute of Health. An algorithm was developed to classify the risk and thus establish possible cases or suspected cases. The risk was established according to the traffic light. Green: Low risk of being infected by SARS COV2, orange: intermediate risk, red: high risk of being infected. Results: The app was used by 3,165 people, 1,893 men and 1,273 women, median age of 37.38 years; 2,026 users between 25-50 years. Algorithm classification was: GREEN: 2,761 cases. RED: 270 cases. >60 years were 23 users and in <60 years were 247. ORANGE: 134 cases >60 years were 11 users and for <60 years 123 cases. Conclusions: The mobile application for the control of a pandemic at the local level is real, economic and has an impact on the follow-up of cases and prioritization of them, in addition to generating an articulation with the different institutions with a cross-sectoral approach; highlighting the success of the mobilization of experts in epidemiology.